2022
DOI: 10.1007/s00248-022-01986-x
|View full text |Cite
|
Sign up to set email alerts
|

Geographical and Seasonal Analysis of the Honeybee Microbiome

Abstract: We previously showed that colonies of thriving and non-thriving honeybees co-located in a single geographically isolated apiary harboured strikingly different microbiomes when sampled at a single time point in the honey season. Here, we profiled the microbiome in returning forager bees from 10 to 12 hives in each of 6 apiaries across the southern half of Ireland, at early, middle, and late time points in the 2019 honey production season. Despite the wide range of geographical locations and forage available, ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…The gut microbiome of honeybees ( Apis mellifera ) was one of the first insect microbiome studied with NGS approaches, and it was proposed as a model for microbiome research [ 61 ]. The great attention and interest raised by the honeybee microbiome has led to a detailed knowledge on its acquirement, diversity, shaping by external factors [ 45 , 62 64 ], and on its function in relation to the brain-gut axis [ 42 , 65 ]. On the other hand, less is known for other pollinators and especially for solitary bees probably because of the difficulties in collection and study.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiome of honeybees ( Apis mellifera ) was one of the first insect microbiome studied with NGS approaches, and it was proposed as a model for microbiome research [ 61 ]. The great attention and interest raised by the honeybee microbiome has led to a detailed knowledge on its acquirement, diversity, shaping by external factors [ 45 , 62 64 ], and on its function in relation to the brain-gut axis [ 42 , 65 ]. On the other hand, less is known for other pollinators and especially for solitary bees probably because of the difficulties in collection and study.…”
Section: Discussionmentioning
confidence: 99%
“…In both panels, the species are ordered within each group according to decreasing prevalence. with the time of the season (Almeida et al, 2023). In another study, the change was found to be very small (Subotic et al, 2019)-which the authors attributed to the high dominance of gut microbes in the overall microbiota of any bee individual (Subotic et al, 2019) and to the proposed stability of gut microbiota over time (Corby-Harris et al, 2014).…”
Section: Spatiotemporal Variation In the Realized Eltonian Niche Of H...mentioning
confidence: 94%
“…to shape the bee microbiota with varying strengths, with impacts ranging from mild (Almeida et al, 2023) to strong (Aizenberg-Gershtein et al, 2013;Muñoz-Colmenero et al, 2020;Subotic et al, 2019). Landscape attributes have also been shown to affect the gut microbiome (Jones et al, 2018).…”
Section: Spatiotemporal Variation In the Realized Eltonian Niche Of H...mentioning
confidence: 99%
“…Since worker age (Hroncova et al, 2015) and seasonality (Almeida et al, 2022) showed effects on honeybee gut microbiome, these factors need to be considered in the data interpretation. Additionally, the limited sampling for each local population might also under-estimate the gut microbe diversity and bring bias into intra-colony variation (Rothman et al, 2018).…”
Section: Gut Microbiome Evolution Under Local Diet Shift In Asian Hon...mentioning
confidence: 99%